Thermal cycling aging effects on the ratcheting behavior of anisotropic conductive film. Issue 4 (7th September 2015) - Gao, Hong; Ma, Jianhua; Gao, Lilan; Yu, Dunji; Sun, Jinsheng
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to determine: how the thermal cycling aging affects the ratcheting behavior of anisotropic conductive adhesive film (ACF); how the loading conditions and loading history affect the ratcheting strain and strain rate of ACF with different thermal cycling aging histories. Design/methodology/approach – The ACF of CP6920F was cured at 190°C in an electro-thermal vacuum drying apparatus for 30 s. The cured specimens were put into the thermal cycling chamber (−40-150°C) for aging to 25, 50, 100, 200 and 500 cycles. A series of uniaxial ratcheting tests of aged ACF after different thermal cycles was carried out under stress control at 80°C. Findings – The ACF subjected to larger number of thermal aging cycles exhibits less ratcheting strain under the same loading conditions. The ACF with the same thermal cycling aging history shows more ratcheting strain and a higher ratcheting strain rate when loaded under a larger mean stress or stress amplitude or a lower loading rate. The ratcheting behavior of aged ACF is found to be more sensitive to the lower loading rate. The higher mean stress (or stress amplitude) enhances the deformation resistance and consequently restrains the ratcheting strain of subsequent cycling with a lower mean stress (or stress amplitude). The prior lower loading rate accelerates the plastic deformation more significantly than the higher one. Originality/value – The influencing trends of thermal cycling aging, loading condition and loading history on ratcheting behavior of ACF are obtained, which is important for the design and safety assessment of ACF joints.